Good sportsperson - good human being - Hosta, Milan (Kinesiologia Slovenica, 2002)
"What is the nature of the good human being?" is a question asked time and only involves good skills, which doesn't necessarily show a good personality, but is also seen under a wider understanding of human flourishing asa good human being. again since Aristotle's virtue ethics. In the human quest for flourishing as a good human being, according to MacIntyre, man has to fulfill two basic conditions; the ability for rational reasoning, and awareness of dependency on and relationships to others. The good for each cannot be achieved without the pursuit of and harmoniying with the good of the social and cultural environment only within which one can flourish. A good human being is one who benefits her or himself and others. This is a matter not only of being good in any given role one has, for judgments we make about that role are always judgments about human flourishing as a whole. While focusing on the virtues and the rational dependency of man, the paper includes a consideration of the sportsperson as an individual, sport as an institution and society as the environment in which all participants, regardless of their role in sport, have to communicate and co-operate. This is the paradigm that allows the sportsperson to flourish as a good human being, and the social foundation for people to flourish in all their beauty and magnificence.
Keywords: etika; filozofija športa; odnosi; osebnostne lastnosti; šport; športniki; vrednote